Density of Araceae in the Saluopa Waterfall Tourism Area, Wera Village, Poso Regency - Gloria Indah; Samsurizal M Suleman; Aan Febriawan; Amelia Buntu; Lestari MP Alibasyah; Hayyatun Mawaddah (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
Araceae is a group of herbaceous plants that grow on land (terrestrial), in water (aquatic), and by climbing on trees (epiphytic). Araceae plants are widely known by the community as ornamental plants commonly found in home gardens; however, they can also be found growing wild in forests. Tropical regions such as Indonesia provide highly suitable habitats for these plants. Approximately 90% of Araceae genera and 95% of their species occur in tropical areas. This study aimed to describe and determine the species density of plants belonging to the Araceae family in Saluopa Waterfall area, Wera Village, Poso Regency. This research employed a quantitative descriptive design using a survey method, with sampling conducted through the belt transect method. The population in this study consisted of all Araceae species found in the Saluopa Waterfall area, Wera Village. The sample included all Araceae individuals recorded along the observation transects. Documentation and specimen collection were carried out for each Araceae species to enable identification based on morphological characteristics, followed by density analysis. The results revealed 10 species belonging to the Araceae family, distributed across nine genera: Aglaonema, Colocasia, Dieffenbachia, Xanthosoma, Homalomena, Schismatoglottis, Rhaphidophora, Scindapsus, and Syngonium. The density values ranged from 0.02 to 0.24 individuals per meter, comprising ten species from nine different genera. The highest density species was Colocasia esculenta (0.24), followed by Homalomena rubescens (0.17) and Dieffenbachia seguine (0.13) while the lowest one was Schismatoglottis calyptrata (0.02).